Kuijieyuan Decoction Improved Intestinal Barrier Injury of Ulcerative Colitis by Affecting TLR4-Dependent PI3K/AKT/NF-κB Oxidative and Inflammatory Signaling and Gut Microbiota - Liu, Baohai; Piao, Xuehua; Niu, Wei; Zhang, Qingyu; Ma, Chi; Wu, Tong; Gu, QiChang; Cui, Tingfang; Li, Shuangdi (Frontiers in Pharmacology, 2020)
Ethnopharmacological relevance In Traditional Chinese medicine (TCM) theory, ulcerative colitis (UC) is associated with damp-heat, blood stasis, and intestinal vascular ischemia. Kuijieyuan decoction (KD) is a traditional Chinese medicine based on the above theory and used clinically to alleviate UC injury. Methods The main components of KD were analyzed by using high-pressure liquid chromatography (HPLC) and confirmed by UPLC-MS/MS. A UC model was established in rats by using dextran sulfate sodium (DSS) and dead rats (caused by DSS) were excluded from the study. Forty-eight rats were divided into 6 groups, health control (CG), UC model (UG), sulfasalazine (SG), low-dose KD (LG), middle-dose KD (MG), and high-dose KD (HG) groups. UC damage was assessed by hematoxylin and eosin staining and scan electron microscopy. We measured Toll-like receptor 4 (TLR4), p-phosphatidylinositol 3-kinase (PI3K), PI3K, p-Protein kinase B (AKT), AKT, p-nuclear factor kappa B (NF-κB), NF-κB, oxidative stress marker (superoxidase dismutase (SOD), catalase (CAT), glutathione peroxidases (GPx), and malondialdehyde) and inflammatory markers (tumor necrosis factor α (TNFα), interleukin (IL)-1, IL-6 and IL-10) in UC tissues. Gut microbiota was analyzed through16S rRNA sequencing. Results The main components of KD consist of gallic acid, paeoniflorin, emodin, berberine, coptisine, palmatine, jatrorrhizine，baicalein and baicalin. The UC model was successfully established by causing intestinal barrier injury with the loss of intestinal villi and destructed mitochondria of intestinal epithelial cells. Both sulfasalazine and KD treatment repaired UC injury, reduced the levels of malondialdehyde, TNFα, IL-1, IL-6, TLR4, p-PI3K, p-AKT, and p-NF-κB, and increased the levels of SOD, GPx, CAT, and IL-10. KD showed a protective function for the UC model in a dose-dependent way. The serum levels of paeoniflorin and baicalin had a strong relationship with the levels of inflammatory and oxidative stress biomarkers. KD treatment increased the proportion of Alloprevotella, Treponema, Prevotellaceae, and Prevotella, and reduced the proportion of Escherichia_Shigella and Desulfovibrio in gut microbiota. Conclusions KD improved intestinal barrier injury of ulcerative colitis, antioxidant and anti-inflammatory properties by affecting TLR4-dependent PI3K/AKT/NF-κB signaling possibly through the combination of its main compounds, and improving gut microbiota.